2017
DOI: 10.1088/1361-6560/aa590a
|View full text |Cite
|
Sign up to set email alerts
|

A model-based 3D patient-specific pre-treatment QA method for VMAT using the EPID

Abstract: This study reports the development and validation of a model-based, 3D patient dose reconstruction method for pre-treatment quality assurance using EPID images. The method is also investigated for sensitivity to potential MLC delivery errors. Each cine-mode EPID image acquired during plan delivery was processed using a previously developed back-projection dose reconstruction model providing a 3D dose estimate on the CT simulation data. Validation was carried out using 24 SBRT-VMAT patient plans by comparing: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…EPID‐based dosimetry has been investigated and developed by many groups. Lee et al compared EPID‐based planar dose map to MapCheck and radiographic film‐based dosimetry and concluded that the EPID‐based approach is appropriate for 2D dose verification, including complex intensity modulated fields; Mans et al, and McCowan et al developed model‐based 3D dose verification process using EPID for VMAT plan; a good review paper by Van Elmpt et al has summarized the utilization of EPID in nontransmission‐based (no phantom or patient) and the transmission‐based (with phantom or patient) measurement for both 2D and 3D dose verification. The major conclusions from those publications are that the use of EPID for dosimetry has matured and a variety of reliable and accurate EPID‐based dose verification programs have been developed and are being used in a growing number of clinics.…”
Section: Discussionmentioning
confidence: 99%
“…EPID‐based dosimetry has been investigated and developed by many groups. Lee et al compared EPID‐based planar dose map to MapCheck and radiographic film‐based dosimetry and concluded that the EPID‐based approach is appropriate for 2D dose verification, including complex intensity modulated fields; Mans et al, and McCowan et al developed model‐based 3D dose verification process using EPID for VMAT plan; a good review paper by Van Elmpt et al has summarized the utilization of EPID in nontransmission‐based (no phantom or patient) and the transmission‐based (with phantom or patient) measurement for both 2D and 3D dose verification. The major conclusions from those publications are that the use of EPID for dosimetry has matured and a variety of reliable and accurate EPID‐based dose verification programs have been developed and are being used in a growing number of clinics.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing use of electronic portal imaging devices such as EPIDose (Sun Nuclear) and Portal Dosimetry (Varian Medical Systems, Palo Alto, CA) QA systems [22,23], it is possible that some private centres will change their clinical QA workflows potentially negating the need for setup dosimeters. The RTs working on the treatment machines are better able to utilise any gaps between patient treatments for the QA procedures.…”
Section: Teaching Of Qa Conceptsmentioning
confidence: 99%
“…Commercially available detector arrays, such as Arc-CHECK (Sun Nuclear Corp., Melbourne, FL), Octavius 4D (PTW, Freiburg, Germany), and Delta4 (Scandidos AB, Upsala, Sweden), compare measured to planned 3D dose distributions. [18][19][20] In 3D transit EPID dosimetry, the dose is reconstructed within the patient or phantom based on EPID measurements acquired behind the patient or phantom. [7][8][9][10][11][12][13][14][15] Although initially developed for patient setup verification, Electronic Portal Imaging Devices (EPIDs) also have useful dosimetric characteristics as summarized in review articles.…”
Section: Introductionmentioning
confidence: 99%
“…In 3D non-transit EPID dosimetry, the dose is determined within the patient or phantom based on in air or fluence EPID measurements, that is, without an attenuating medium between the source and the detector. [18][19][20] In 3D transit EPID dosimetry, the dose is reconstructed within the patient or phantom based on EPID measurements acquired behind the patient or phantom. [21][22][23][24][25] A clear advantage of EPIDs is their availability which makes them suitable for large scale implementations.…”
Section: Introductionmentioning
confidence: 99%